Family‐Focused Therapy for Bipolar Disorder: Reflections on 30 Years of Research. Issue 3 (29th July 2016) - Miklowitz, David J.; Chung, Bowen
Abstract : Family‐focused therapy (FFT) is an evidence‐based intervention for adults and children with bipolar disorder (BD) and their caregivers, usually given in conjunction with pharmacotherapy after an illness episode. The treatment consists of conjoint sessions of psychoeducation regarding bipolar illness, communication enhancement training, and problem‐solving skills training. This paper summarizes over 30 years of research on FFT and family processes in BD. Across eight randomized controlled trials with adults and adolescents with BD, FFT and mood‐stabilizing medications have been found to hasten recovery from mood episodes, reduce recurrences, and reduce levels of symptom severity compared to briefer forms of psychoeducation and medications over 1–2 years. Several studies indicate that the effects of FFT on symptom improvement are greater among patients with high‐expressed emotion relatives. New research focuses on FFT as an early intervention for youth at risk for BD, neuroimaging as a means of evaluating treatment mechanisms, and progress in implementing FFT in community mental health settings.